Alternans in Genetically Modified Langendorff-Perfused Murine Hearts Modeling Catecholaminergic Polymorphic Ventricular Tachycardia - Sabir, Ian N.; Ma, Nan; Jones, Victoria; Goddard, Catharine A.; Zhang, Yanmin; Kalin, Asli; Grace, Andrew; Huang, Christopher (Frontiers in Physiology, 2010)
The relationship between alternans and arrhythmogenicity was studied in genetically modified murine hearts modeling catecholaminergic polymorphic ventricular tachycardia (CPVT) during Langendorff perfusion, before and after treatment with catecholamines and a β-adrenergic antagonist. Heterozygous (RyR2p/s) and homozygous (RyR2s/s) RyR2-P2328S hearts, and wild-type (WT) controls, were studied before and after treatment with epinephrine (100 nM and 1 µM) and propranolol (100 nM). Monophasic action potential recordings demonstrated significantly greater incidences of arrhythmia in RyR2s/p and RyR2s/s hearts as compared to WTs. Arrhythmogenicity in RyR2s/s hearts was associated with alternans, particularly at short baseline cycle lengths. Both phenomena were significantly accentuated by treatment with epinephrine and significantly diminished by treatment with propranolol, in full agreement with clinical expectations. These changes took place, however, despite an absence of changes in action potential durations, ventricular effective refractory periods or restitution curve characteristics. Furthermore pooled data from all hearts in which arrhythmia occurred demonstrated significantly greater alternans magnitudes, but similar restitution curve slopes, to hearts that did not demonstrate arrhythmia. These findings thus further validate the RyR2-P2328S murine heart as a model for human CPVT, confirming an alternans phenotype in common with murine genetic models of the Brugada syndrome and the congenital long-QT syndrome type 3. In contrast to these latter similarities, however, this report demonstrates the dissociation of alternans from changes in the properties of restitution curves for the first time in a murine model of a human arrhythmic syndrome.